2009
DOI: 10.1007/s11604-008-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain magnetic resonance findings in infective endocarditis with neurological complications

Abstract: The MRI findings associated with infective endocarditis are wide-ranging: embolization, hemorrhage, meningitis, cerebritis, abscess, the bull's-eye-like lesion. Clinicians should consider the possibility of infective endocarditis in patients with unknown fever and neurological abnormality. Brain MRI should be promptly performed for those patients, and T2*-weighted imaging is recommended for an early diagnosis of infective endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…MRI also demonstrated a neuroimaging embolism spectrum. Several years ago, Singhal et al, Barsic et al, and Okazaki et al noted the predominance of smaller lesions [ 14 16 ], which, instead, affect cortical and border zone arterial territories [ 17 ]. Similarly, Hess et al, on 109 prospective cases without neurologic symptoms, emphasized the frequency of acute ischemic lesions and of small infarcts widespread in watershed territories [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI also demonstrated a neuroimaging embolism spectrum. Several years ago, Singhal et al, Barsic et al, and Okazaki et al noted the predominance of smaller lesions [ 14 16 ], which, instead, affect cortical and border zone arterial territories [ 17 ]. Similarly, Hess et al, on 109 prospective cases without neurologic symptoms, emphasized the frequency of acute ischemic lesions and of small infarcts widespread in watershed territories [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…CT is not able to detect CMBs. This hypointense T2*-weighted MRI round or ovoid signal with a diameter <10 mm can be detected in elderly patients and, overall, in small-vessel disease such as arteriolosclerosis, chronic hypertension, amyloid angiopathy, as well as Alzheimer’s disease [ 13 , 17 ]. They notably have a strong specific IE association.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of detecting embolic lesions in the brain or spine may depend on the institute and country. The previous cohort from Japan showed that 93% of IE patients with neurological abnormality had intracranial abnormalities on head MRI (hemorrhage in three and abscess formation in three) [ 24 ]. The authors concluded that MRI should be promptly performed on IE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hypointense signal spots on T2*-weighted MRI are also observed in chronic hypertension, changes of an arteriosclerotic nature, and amyloid angiopathy. 21, 22 In a crosssectional study of 1,965 elderly subjects in Framingham, 78% of the patients with hypointense signal spots had hypertension, and the prevalence of patients with hypointense signal spots increased with age. 23 In our study, only 41% patients with hypointense signal spots had hypertension, and hypointense signal spots appeared in patients with regardless of age.…”
Section: Funding Sourcesmentioning
confidence: 99%